Exposure to airborne particulate matter induces renal tubular cell injury in vitro: the role of vitamin D signaling and renin-angiotensin system. Issue 8 (August 2022) - Kang, Eungu; Yim, Hyung Eun; Nam, Yoon Jeong; Jeong, Sang Hoon; Kim, Joo-Ae; Lee, Ju-Han; Son, Min Hwa; Yoo, Kee Hwan
Abstract: Background: Exposure to air pollution can interfere with the vitamin D endocrine system. This study investigated the effects of airborne particulate matter (PM) on renal tubular cell injury in vitro and explored the underlying mechanisms. Methods: HK-2 human renal proximal tubule cells were treated with PM with or without 1, 25(OH)2 D3 analog, 19-Nor-1, 25(OH)2 D2 (paricalcitol, 10 nM) for 48 h. The dose- and time-dependent cytotoxicity of PM with or without paricalcitol was determined via cell counting kit-8 assay. Cellular oxidative stress was assessed using commercially available enzyme-linked immunosorbent assay kits. The protein expression of vitamin D receptor (VDR), cytochrome P450(CYP)27B1, CYP24A1, renin, angiotensin converting enzyme (ACE), angiotensin II type 1 receptor (AT1), nuclear factor erythroid 2-related factor 2 (Nrf2), nuclear factor-kB (NF-kB), tumor necrosis factor (TNF)-α, and interleukin (IL)-6 was determined. Results: PM exposure decreased HK-2 cell viability in a dose- and time-dependent manner. The activities of superoxide dismutase and malondialdehyde in HK-2 cells increased significantly in the group exposed to PM. PM exposure decreased VDR and Nrf2, while increasing CYP27B1, renin, ACE, AT1, NF-kB, TNF-α, and IL-6. The expression of VDR, CYP27B1, renin, ACE, AT1, and TNF-α was reversed by paricalcitol treatment. Paricalcitol also restored the cell viability of PM-exposed HK-2 cells. Conclusion: Our findings indicate that exposure to PM induces renal proximal tubular cell injury, concomitant with alteration of vitamin D endocrine system and renin angiotensin system. Vitamin D could attenuate renal tubular cell damage following PM exposure by suppressing the renin-angiotensin system and by partially inhibiting the inflammatory response. Abstract : Airborne particulate matter; Kidney tubules; Renin-angiotensin system; Vitamin D deficiency.